2021
DOI: 10.3389/fimmu.2021.788406
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Functional Alteration of Mucosal-Associated Invariant T Cells in Adult Patients With Community-Acquired Pneumonia

Abstract: Community-acquired pneumonia (CAP) remains the significant infectious cause of morbidity and mortality worldwide. Although mucosal-associated invariant T cells (MAIT) play roles in the pathogenesis of children CAP and ICU-associated pneumonia, their roles in adult CAP are largely unexplored. In this study, we investigated the frequency, phenotype, and function of MAIT cells in peripheral blood and bronchoalveolar lavage fluid (BALF) of adult CAP patients. Our data indicate that MAIT-cell frequency is profoundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The frequency of MAIT cells that produce IFN‐γ and TNF‐α was examined by intracellular staining flow cytometry (Kim et al, 2022; Ouyang et al, 2021). Freshly isolated peripheral blood mononuclear cells (PBMCs) were used for functional assays.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of MAIT cells that produce IFN‐γ and TNF‐α was examined by intracellular staining flow cytometry (Kim et al, 2022; Ouyang et al, 2021). Freshly isolated peripheral blood mononuclear cells (PBMCs) were used for functional assays.…”
Section: Methodsmentioning
confidence: 99%
“…81 Synthesis of proinflammatory signaling molecules during pneumonia increases recruitment of leukocytes to the tissue that aids in pathogen clearance. Key recruited leukocytes that play a role in antimicrobial defence are neutrophils, alveolar macrophages, recruited monocytes, dendritic cells, natural killer cells, mucosaassociated invariant T cells, T cells, and B cells, [82][83][84] in addition to epithelial cells that play an important role in regulating acute and adaptive immunity. [85][86][87] Downstream of TLR and other PRR activation, phospholipases are activated and metabolize membrane phospholipids to produce AA.…”
Section: Proinflammatory Phase Of the Inflammatory Response To Infectionmentioning
confidence: 99%
“…Community-acquired pneumonia (CAP) is still an important infectious cause of mortality and morbidity worldwide caused by a wide variety of micro-organisms including bacteria, fungi and virus [1]. The host innate and adaptive immune responses play crucial roles in the pathological processes of CAP and determine disease severity [2][3][4]. Previous studies have demonstrated that the dysregulation of T cells, neutrophils and macrophages are involved in CAP [2][3][4].…”
Section: Introductionmentioning
confidence: 99%